155k views
0 votes
Instructions: Use the ratio of a 45-45-90 triangle to solve for the variables. Leave your answers as radicals in simplest form.

Instructions: Use the ratio of a 45-45-90 triangle to solve for the variables. Leave-example-1
Instructions: Use the ratio of a 45-45-90 triangle to solve for the variables. Leave-example-1
Instructions: Use the ratio of a 45-45-90 triangle to solve for the variables. Leave-example-2

2 Answers

3 votes

Answer:n

Step-by-step explanationaa:

User Sunmat
by
5.0k points
4 votes

The answers are:

- For the first triangle:
\( u = 6 \), \( v = 6√(2) \)

- For the second triangle:
\( x = 13√(2) \), \( y = 13 \)

In both triangles, we'll use the properties of a 45-45-90 triangle. In such a triangle, the sides are in the ratio
\( 1:1:√(2) \), meaning the legs are congruent, and the hypotenuse is
\( √(2) \)times the length of a leg.

For the first triangle with a leg of 6 units:

- Let the legs be of length a .

- Then the hypotenuse v will be
\( a√(2) \).

- Given that one leg a = 6 , the hypotenuse
\( v = 6√(2) \).

For the second triangle with a hypotenuse of
\( 13√(2) \) units:

- Let the legs be of length y and the hypotenuse be x .

- Using the ratio for a 45-45-90 triangle, we have
\( x = y√(2) \).

- Given that the hypotenuse
\( x = 13√(2) \), we can find the leg y by dividing the hypotenuse by
\( √(2) \), resulting in \( y = (13√(2))/(√(2)) = 13 \).

So for the first triangle, u = 6 and
\( v = 6√(2) \). For the second triangle,
\( x = 13√(2) \) and \( y = 13 \).These are the sides' lengths in radical form in their simplest terms. Since the system has been reset, I'll re-execute the code to provide the necessary mathematical operations to confirm these results.

For the first triangle, the leg is given as 6 units, so the hypotenuse
\( v \) is \( 6√(2) \).

For the second triangle, with a hypotenuse given as
\( 13√(2) \) units, the length of each leg \( y \) is 13 units.

User Dmitry Savy
by
4.3k points